Collections coloniales? L'implication de la Suisse dans le processus d'expansion coloniale européen au siècle des Lumières - Brizon, Claire (Swiss Journal of Sociocultural Anthropology, 2019)
Based on three case studies of artifacts from 18th century collections preserved in Swiss cultural institutions, I attempt to rethink the use of the word "colonial" before the 19th century, and to apply it to describe collections from the modern period. I attempt to shed light on how these collections could be exhibited to provide critical perspective on these artefacts and the stories they are allowed to tell, in view of the upcoming exhibition entitled Exotic Switzerland? A Global History of the Enlightenment to open in 2020 at the Palais de Rumine in Lausanne.